AdS₄ x CP³ superstring as OSp(4|6)/(SO(1,3) x U(3)) sigma-model in conformal basis - Uvarov, D.V. (Вопросы атомной науки и техники, 2012)
Basic features of Lagrangian formulation for AdS₄ x CP³ superstring in the framework of OSp(4|6)/(SO(1,3) x U(3)) sigma-model approach are reviewed with the emphasis on realization osp(4|6) background isometry superalgebra as D = 3 N = 6 superconformal algebra.